1997
DOI: 10.1099/00221287-143-10-3085
|View full text |Cite
|
Sign up to set email alerts
|

Low-resolution sequencing of Rhodobacter sphaeroides 2.A.1T: chromosome II is a true chromosome

Abstract: The photosynthetic bacterium Rhodobseter sphsemides 2.4.V has two chromosomes, CI (-39 Mb) and CII (-09 Mb). In this study a low-redundancy sequencing strategy was adopted to analyse 23 out of 47 cosmids from an (dORFs). A total of 144 strong matches to the database was found; 101 of these matches represented genes encoding a wide variety of functions, e.g. amino acid biosynthesis, photosynthesis, nutrient transport and various regulatory functions. Two rRNA operons ( m B and mC) and five tRNAs were also iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
21
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…Since early genetic work on Escherichia coli established the dogma of a single circular chromosome in prokaryotes, essentially all smaller replicons in cells have been relegated to the status of extrachromosomal elements or plasmids, irrespective of the species (Drlica and Riley 1990). Of the many plasmids that have been characterized, several are megaplasmids from a hundred kilobases to megabase sizes, including F (fertility) and R (resistance) factors, and toxin-bearing plasmids in E. coli and other pathogenic bacteria (Proter 1991), tumor-inducing plasmids and symbiotic plasmids in Agrobacterium and Rhizobium species (Van Larebeke et al 1974;Banfalvi et al 1985), and a variety of aromatic hydrocarbon degradation plasmids in Pseudomonas species and related bacteria (Franz and Chakrabarty 1986;Choudhary et al 1997;Mouncey et al 1997).…”
mentioning
confidence: 99%
“…Since early genetic work on Escherichia coli established the dogma of a single circular chromosome in prokaryotes, essentially all smaller replicons in cells have been relegated to the status of extrachromosomal elements or plasmids, irrespective of the species (Drlica and Riley 1990). Of the many plasmids that have been characterized, several are megaplasmids from a hundred kilobases to megabase sizes, including F (fertility) and R (resistance) factors, and toxin-bearing plasmids in E. coli and other pathogenic bacteria (Proter 1991), tumor-inducing plasmids and symbiotic plasmids in Agrobacterium and Rhizobium species (Van Larebeke et al 1974;Banfalvi et al 1985), and a variety of aromatic hydrocarbon degradation plasmids in Pseudomonas species and related bacteria (Franz and Chakrabarty 1986;Choudhary et al 1997;Mouncey et al 1997).…”
mentioning
confidence: 99%
“…Studies from our laboratory revealed that R. sphaeroides 2.4.1 T possesses two different circular chromosomes, of ϳ3.0 Mbp (CI) and ϳ0.9 Mbp (CII) (42,43). A number of genes have been shown to be duplicated between CI and CII (5). In contrast, we have previously shown by Tn5 mutagenesis that some pathways, e.g., p-aminobenzoic acid, uracil, histidine, and thymine biosynthesis, are partitioned rather than duplicated between CI and CII (4).…”
mentioning
confidence: 99%
“…Recently, we used a low-redundancy sequencing strategy for analysis of the genetic content of CII (5). We analyzed ϳ300 kb of unique DNA which identified approximately 200 putative open reading frames (ORFs) representing a wide variety of functions, e.g., amino acid biosynthesis, nutrient transporters, redox-active systems, and a number of regulatory functions, indicating that CII does not contain genes specialized for any particular metabolic function, physiologic state, or growth condition.…”
mentioning
confidence: 99%
“…CI and CII are 3,188,631 and 943,022 bp long, respectively, and contain approximately 3,106 and 874 open reading frames, respectively. Preliminary genome analyses (5,6,25,26) have revealed that a wide variety of essential and housekeeping genes are present on both CI and CII.…”
mentioning
confidence: 99%